Pharmacoepidemiological rationale for the use of antibacterial drugs in community-acquired pneumonia in children of different ages - Kodirova Shakhlo Salokhitdinovna (Journal of Science in Medicine and Life, 2024)
Global recommendations for the treatment strategy of community-acquired pneumonia are antibacterial therapy (ABT) - beta-lactams, fluoroquinolones, macrolides - until the results of laboratory tests are available to identify the etiological agent responsible for CAP. etiotropic therapy. According to Russian national clinical guidelines, macrolides, fluoroquinolones, cephalosporins and aminopenicillins are prescribed empirically. Meta-analyses have found better outcomes in patients treated with a combination of macrolides and beta-lactams compared to beta-lactams alone. However, the clinical benefit of adding macrolides to beta-lactams for the empiric treatment of moderate SAP remains controversial, as the difference in treatment results may depend on the age and comorbid conditions of the patients.